Differential impact of unilateral stroke on the bihemispheric motor cortex representation of the jaw and tongue muscles in young and aged rats - Cullins, Miranda J.; Connor, Nadine P. (Frontiers in Neurology, 2024)
Introduction Dysphagia commonly occurs after stroke, yet the mechanisms of post-stroke corticobulbar plasticity are not well understood. While cortical activity associated with swallowing actions is bihemispheric, prior research has suggested that plasticity of the intact cortex may drive recovery of swallowing after unilateral stroke. Age may be an important factor as it is an independent predictor of dysphagia after stroke and neuroplasticity may be reduced with age. Based on previous clinical studies, we hypothesized that cranial muscle activating volumes may be expanded in the intact hemisphere and would contribute to swallowing function. We also hypothesized that older age would be associated with limited map expansion and reduced function. As such, our goal was to determine the impact of stroke and age on corticobulbar plasticity by examining the jaw and tongue muscle activating volumes within the bilateral sensorimotor cortices. Methods Using the middle cerebral artery occlusion rat stroke model, intracortical microstimulation (ICMS) was used to map regions of sensorimotor cortex that activate tongue and jaw muscles in both hemispheres. Young adult (7 months) and aged (30 months) male F344 × BN rats underwent a stroke or sham-control surgery, followed by ICMS mapping 8 weeks later. Videofluoroscopy was used to assess oral-motor functions. Results Increased activating volume of the sensorimotor cortex within the intact hemisphere was found only for jaw muscles, whereas significant stroke-related differences in tongue activating cortical volume were limited to the infarcted hemisphere. These stroke-related differences were correlated with infarct size, such that larger infarcts were associated with increased jaw representation in the intact hemisphere and decreased tongue representation in the infarcted hemisphere. We found that both age and stroke were independently associated with swallowing differences, weight loss, and increased corticomotor thresholds. Laterality of tongue and jaw representations in the sham-control group revealed variability between individuals and between muscles within individuals. Conclusion Our findings suggest the role of the intact and infarcted hemispheres in the recovery of oral motor function may differ between the tongue and jaw muscles, which may have important implications for rehabilitation, especially hemisphere-specific neuromodulatory approaches. This study addressed the natural course of recovery after stroke; future work should expand to focus on rehabilitation.